Development and pilot testing of a radiation therapist-led educational intervention for breast cancer patients prior to commencing radiotherapy - Halkett, Georgia; Schofield, P.; O'Connor, Moira; York, D.; Jefford, M.; Jiwa, Moyez; Spry, Nigel; Taylor, A.; Aranda, S. (Blackwell Publishing, 2012)
Methods: A tailored intervention consisting of two face-to-face meetings with a radiation therapist (one before radiation planning, the other before treatment) was developed using Level I evidence for preparing patients for potentially threatening procedures. Training of intervention radiation therapists consisted of two communication skills workshops. Radiation therapists’ consultations were tape-recorded and analyzed. The feasibility of the intervention was assessed by response rates and feedback from patients and radiation therapists. Patients completed surveys at baseline and following each intervention delivery. The main outcome measures were anxiety and depression, patient concerns and knowledge about radiotherapy. Results: Response rates were considered acceptable. Twelve patients were enrolled and completed baseline measures. Nine patients completed follow-up measures following the second consultation. Preliminary results showed a trend for a decrease in anxiety and depression levels following the first consultation. There was also a decrease in concerns about radiotherapy and an increase in patients’ knowledge. The instruments showed variability at baseline and discriminated between different responses over time. Radiation therapists adhered to providing the interventions. Interviews with radiation therapists and patients demonstrated that the intervention was feasible and acceptable. Conclusion: This pilot study demonstrated that this new intervention is both feasible and acceptable to radiation therapists and patients. The intervention is now being assessed using a randomized controlled trial.